European Shakespeares. Translating Shakespeare in the Romantic Age : Translating Shakespeare in the Romantic Age - Selected Papers from the Conference on Shakespeare Translation in the Romantic Age, University of Antwerpen, 19-21 April 1990. - Delabastita, Dirk (John Benjamins Pub. Co., 1993)
Where, when, and why did European Romantics take to Shakespeare? How about Shakespeare's reception in enduring Neoclassical or in popular traditions? And above all: which Shakespeare did these various groups promote? This collection of essays leaves behind the time-honoured commonplaces about Shakespearean translation (the 'translatability' of Shakespeare's forms and meanings, the issue of 'loss' and 'gain' in translation, the distinction between 'translation' and 'adaptation', translation as an 'art'. etc.) and joins modern Shakespearean scholarship in its attempt to lay bare the cultural mec.